Face-to-face and internet-based cognitive therapy for social anxiety disorder: Mechanisms of change and treatment dissemination - Thew, GR (2018)
While effective psychological interventions for common mental health difficulties exist, our understanding of how they work, and our ability to disseminate them at scale, is limited. This thesis aimed to 1) examine the mechanisms underlying clinical improvement in one such intervention, Cognitive Therapy for Social Anxiety Disorder (CT-SAD), and 2) disseminate and evaluate an internet-based version (iCT-SAD) in a new culture (Hong Kong). Following an introduction and literature review (Chapters 1 and 2), eight studies are presented. Studies 1, 2a, and 2b (Chapters 3 and 4) investigated three candidate mediators (negative social cognitions, self-focused attention, and depressed mood) of the relationship between time in therapy and social anxiety symptoms. Results indicated that cognitions consistently mediated subsequent clinical improvement, with weaker and less consistent effects for self-focused attention and depressed mood. Studies 3a, 3b, and 3c (Chapter 5) examined ‘sudden gains’: large and stable symptom reductions between consecutive therapy sessions, in CT-SAD and iCT- SAD. Sudden gains were common in both treatments, occurring with similar frequency and magnitude. They were associated with better overall therapy outcome. There was some evidence of reductions in negative cognitions and self- focused attention prior to, and concurrently with, gains. Clients in CT made more statements indicating ‘generalised’ learning in ‘pre-gain’, relative to control, sessions. Study 4 (Chapter 6) implemented a new iCT-SAD therapist training programme with three therapists from Hong Kong, who delivered the treatment in a pilot case series. Study 5 (Chapter 7) then evaluated the efficacy of iCT-SAD in Hong Kong compared to waitlist controls in a randomized controlled trial. Results indicated the training was effective at developing iCT skills and competence, and that iCT-SAD was superior to waitlist, showing large effect sizes comparable to UK studies. Implications for theory, research, and practice are discussed (Chapter 8). Overall, the findings indicate that negative social cognitions play an important role in determining clinical improvement in CT-SAD and iCT-SAD, that the therapy mechanisms of change investigated appear to be similar between these treatment formats, and that iCT-SAD was successfully disseminated to another culture without losing efficacy.